Relevansi Kesetaraan Gender dan Peran Perempuan Bekerja terhadap Kesejahteraan Keluarga di Indonesia (Perspektif Ekonomi Islam) - Putri Dyah Ayu Fitriyaningsih; Fita Nurotul Faizah Munawan (LPPM IAIN Parepare, 2020)
This study aims to identify problems related to the relevance of gender equality and the status of working women to family welfare in Indonesia based on an Islamic economic perspective. This study uses descriptive qualitative research methods with secondary data provided is documentation. The results of this study indicates that there is no dichotomy of public space for women and men in work. Both have the same rights and obligations. Islam as a religion rahmatan lil alamin also expressly explains about human freedom to work and cooperate in